Front Cover: Selective Borylation of [4]Helicene (Eur. J. Org. Chem. 34/2016). Issue 34 (December 2016) - Nečas, David; Kaiser, Reinhard P.; Ulč, Jan
Abstract : The cover picture shows an old, stone‐made, spiral staircase that resembles the unique helical structure of helicenes. Despite the fact that helicenes are known for more than 100 years, their chemistry of post‐functionalization is still significantly underdeveloped. This lack of "tools" limits the synthesis and exploration of the distinctive optoelectrical properties of new materials based on carbohelicenes. Details on the post‐functionalization of [4]helicene by a C–H activation/borylation process are discussed in the article by D. Nečas, et al. onp. 5647 ff .